Trends and determinants of social inequities in cardiovascular risk factors in Spain: a mixed-methods study - Julia Díez; Guillermo Taulet; Mario Fontán-Vela; Yolanda González-Rábago; Luis Cereijo; María Sandín-Vázquez; Elena Rodríguez; Manuel Franco; Carme Borrell; Usama Bilal; Pedro Gullón (Elsevier, 2023)
This sequential mixed-methods study aims to: 1) assess spatial and temporal trends in cardiovascular risk factors by socioeconomic position from 2001 to 2020 in Spain; 2) explore public health professionals' perspectives regarding interventions that might have impacted these inequities; and 3) analyze determinants on social inequities in cardiovascular risk factors. First, we will measure the change in absolute and relative social inequities in eight cardiovascular risk factors through time trend analysis using repeated cross-sectional data from both National and European Health Surveys for Spain from 2001 to 2020. Second, we will interview key informants -both at the regional and national level-, to contextualize data obtained in phase 1 and capture the content and variation of policies across regions. Third, we will use econometric methods to analyze how these identified interventions have impacted these social inequities within and across regions. Resumen: Este estudio tiene por objetivos: 1) evaluar las tendencias espacio-temporales de los factores de riesgo cardiovascular en España, por posición socioeconómica, entre 2001 y 2020; 2) explorar las perspectivas de profesionales salubristas con respecto a las intervenciones que pueden influir en estas inequidades; 3) analizar los determinantes de las inequidades sociales en los factores de riesgo cardiovascular. Primero se medirá el cambio en las desigualdades, en términos absolutos y relativos, según ocho factores de riesgo mediante un análisis de tendencias temporales y datos de las encuestas nacionales y europeas de salud para España entre 2001 y 2020. Después se entrevistará a informantes clave, en los ámbitos de comunidad autónoma y nacional, para contextualizar los datos obtenidos en la primera fase y explorar la variabilidad entre comunidades autónomas. Por último, se analizará mediante métodos econométricos cómo influyen dichas intervenciones en las desigualdades sociales entre comunidades autónomas.